The Impact of Commodity Market Volatility on Monetary Policy in Indonesia: A Global Perspective - Nabila, Maulina; Widianingsih (Asosiasi Persatuan Pengusaha Muda Teknik Informatika, 2025)
Commodity market volatility has been a significant challenge for monetary policy in many countries, including Indonesia. The increase in commodity prices, especially oil and foodstuffs, has the potential to affect inflation and people's purchasing power. This study aims to analyze the impact of commodity market volatility on monetary policy in Indonesia and understand the policy response taken by Bank Indonesia in dealing with these fluctuations. The methods used in this study include multiple regression analysis to measure the relationship between commodity price volatility and inflation, as well as a Vector Autoregression (VAR) model to evaluate the interest rate policy response. The results show that commodity price volatility has a significant positive impact on inflation in Indonesia, with each increase in price volatility contributing to an increase in inflation. In addition, Bank Indonesia needs to respond proactively through interest rate adjustments to maintain economic stability. This research contributes important insights for policymakers on the importance of monitoring global commodity markets and developing diversification strategies to mitigate negative impacts on the domestic economy.